Anthraquinone Glycoside from Stem Bark of Cassia reingera and Use of Aqueous Bark Extracts as An Eco-friendly Natural Dye on Wool - Ledwani, Lalita; Sehgal, S.; Gupta, K.C. (Asian Journal of Chemistry, 2010)
From the bark of Cassia reingera 1,5,6-trihydroxy-3-methyl anthraquinone- 8-O-L-glycoside has been isolated and its structure elucidated with the help of chemical studies and spectral data. The dyeing property of crude anthraquinone has been studied to develop variety of shades on wool by dyeing with different mordants.